TANGGUNG JAWAB ROZA KARYA ATAS KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP TENAGA KERJANYA - Lurias Anggun Sari; Hasnuldi Miaz; Jasman Nazar (Ensiklopedia of Journal, 2023)
Occupational Safety and Health ("OSH") is one of the important factors that can affect employee productivity. In carrying out work, it is always possible for the risk of work accidents to occur. Roza Karya is a company that provides and distributes sacrificial animals based on the Al-Quran and Sunnah, Working on farms has various OHS risks quite high, what cows do is unpredictable when workers are nearby. Cattle with a large size can easily injure and kill humans. Based on law number 1 of 1970, OHS must be implemented in all companies, workplaces, and articles 86 and 87 of law number 13 of 2003 concerning manpower also regulate OHS which aims to protect and ensure the safety of every worker and other people in the workplace and Government Regulation number 44 of 2015 concerning the organizers of work accident insurance programs and death insurance with various benefits so that workers can be guaranteed their rights. This research aims to find out how Roza Karya's form of responsibility for occupational safety and health (K3) to its workforce and the obstacles and problems in implementing K3 in its company environment. Based on the results of the study, it can be seen that Roza Karya has implemented an OHS program, but its implementation has violations experienced by workers such as work negligence, as well as environmental factors or unexpected things. The form of responsibility has been pursued by Roza Karya starting from the occurrence of minor work accidents with the presence of a first aid kit as a form of first aid. For moderate work accidents will be handled by the company's OHS experts and in the event of a severe work accident will be referred to the hospital in order to get more optimal service. It is hoped that with this research, the company and the workforce together implement SOP k3 such as wearing Personal Protective Equipment (PPE) while working to avoid the risk of work accidents.Keywords: Responsibility, OHS, Company and Labor